X-ray diffraction study of n-(alkyloxybenzilidene)-n'-toluidines. (12th October 2016) - Kuz'mina, L. G.; Navasardyan, M. A.; Churakov, A. V.; Howard, J. A. K.
ABSTRACT: Liquid crystal n-(alkyloxybenzilidene)-n'-toluidines R−O−C6 H4 −CH = N−C6 H4 −CH3 (R = C9 H20 1 and C10 H21 2) have been investigated by single crystal X-ray structural analysis. The investigation of2 has been performed at different temperatures (120, 295, 320, and 333 K). Both compounds undergo the crystal–smectic–nematic–isotropic phase transitions. Crystal packing of the compounds consists of alternating loosely packed aliphatic and closely packed aromatic areas that involve weak directional π…π stacking interactions and weak O…H−C hydrogen bonds. A possible mechanism of the phase transitions in these compounds based on peculiarities of their crystal packings is discussed.